The BFN mainstreaming toolkit. A roadmap to using neglected and underutilized species for food system change - Borelli, Teresa; Beltrame, Daniela; Wasike, Victor W.; Samarasinghe, Gamini; Tan, Ayfer; Hunter, Danny (Routledge, 2021)
This chapter describes the stepwise approach to biodiversity mainstreaming tested by Brazil, Kenya, Sri Lanka and Turkey during the implementation of the GEF-supported Biodiversity for Food and Nutrition project. Using practical examples, it captures the fundamentals steps needed to integrate neglected and underutilised species into sectoral policies and practices, including how to facilitate and align activities to support achieving national targets linked to biodiversity conservation and food and nutrition security.